Analisis Putusan Pengadilan Negeri Mataram No.222/Pdt.G/2020/Pn Mtr Tentang Perbuatan Ingkar Janji (Wanprestasi) Dalam Pembayaran Sisa Hutang Atas Pembelian Hotel Lima Satu - Rohmatullah, M. Romdhani; Fathoni, M. Yazid (Faculty of Law, University of Mataram, 2024)
This research aims to determine the act of breaking promises (default) in paying the remaining debt for the purchase of the Lima One Hotel Case Number 222/Pdt.G/2020/Pn. Mtr. This type of research is normative law, with a Statute Approach, a Conceptual approach and a Case Approach. The dispute resolution process is carried out by billing the debtor first; if this is not successful, a summons warning letter will be issued. However, if it is still successful, a lawsuit will be filed at the Mataram District Court. The Judge's considerations in handing down a Decision on the Case of Broken Promise (Default) in Payment of the Remaining Debt for the Purchase of the Lima Satu Hotel are divided into 2 (two), namely Juridical considerations and Non-Judicial considerations.